Brain Abscesses in Children: Results of 24 Children From a Reference Center in Central Anatolia, Turkey. (March 2015) - Canpolat, Mehmet; Ceylan, Ozgur; Per, Huseyin; Koc, Gonca; Tumturk, Abdulfettah; Kumandas, Sefer; Patiroglu, Turkan; Doganay, Selim; Gumus, Hakan; Unal, Ekrem; Kose, Mehmet; Gorkem, Sureyya Burcu; et al.
Childhood brain abscesses are a rare and potentially life-threatening condition requiring urgent diagnosis and treatment. This retrospective study analyzed the clinical and radiologic findings of 24 (7 girl, 17 boys) cases with brain abscess. Mean age was 92.98 ± 68.04 months. The most common presenting symptoms were nausea-vomiting (45.8%) and headache (41.7%). Brain abscess was most commonly located in the frontal region. Diffusion restriction was determined in 78.4% of lesions. The mean apparent diffusion coefficient value in these lesions was 0.511 ± 0.23 × 10 –3 mm 2 /s. Cultures were sterile in 40% of cases. Antimicrobial therapy was given to only 16.7% of cases. Predisposing factors were identified in 91.6% of cases (congenital heart disease in 20.8% and immunosuppression in 20.8%). Mortality level was 12.5%. In conclusion, immunocompromised states, and congenital heart disease have become an important predisposing factor for brain abscesses. Effective and prompt management should ensure better outcome in childhood.